PELATIHAN PENYUSUNAN PERINGKAT DAN PROFIL PRESTASI BELAJAR SISWA BAGI GURU SEKOLAH DASAR - Kusmaryono, Imam; Ubaidah, Nila; Basir, Abdul; Maharani, Hevy Risqi; Wijayanti, Dyana; Aminudin, Mohamad (Jurnal Berdaya Mandiri, 2025)
The activity of compiling rankings and profiles of student learning achievement is often carried out when teachers compile end-of-semester learning reports. However, the specific skills and practices of teachers that contribute to differences in determining rankings and profiles of student learning achievement are not well understood. In order to overcome this problem, community service activities were carried out by the faculty of teacher training and education, Sultan Agung Islamic University. The activity was packaged in the form of training in compiling rankings and profiles of student learning achievement using the Z-score method. The implementation of the activity was carried out through the following steps: (a) preparation, (b) implementation, and (c) evaluation. The training participants were 30 elementary school teachers in Rowosari sub-district, Kendal district. The results of the activity showed that 100% of participants were able to compile rankings and profiles of learning achievement correctly. Meanwhile, the results of the questionnaire of 90% of respondents stated that the training material was very useful for teachers. Keywords: training, ranking, learning achievement, elementary school